Implementation of an enhanced recovery protocol in gynecologic oncology - Tanvi V. Joshi; Shaina F. Bruce; Rod Grim; Tommy Buchanan, Jr; Sudeshna Chatterjee-Paer; Elizabeth R. Burton; Joel I. Sorosky; Mark S. Shahin; Mitchell I. Edelson (Elsevier, 2021)
Enhanced Recovery after Surgery (ERAS) is an evidence-based approach that aims to reduce narcotic use and maintain anabolic balance to enable full functional recovery. Our primary aim was to determine the effect of ERAS on narcotic usage among patients who underwent exploratory laparotomy by gynecologic oncologists. We characterized its effect on length of stay, intraoperative blood transfusions, bowel function, 30-day readmissions, and postoperative complications. A retrospective cohort study was performed at Abington Hospital-Jefferson Health in gynecologic oncology. Women who underwent an exploratory laparotomy from 2011 to 2016 for both benign and malignant etiologies were included before and after implementation of our ERAS protocol. Patients who underwent a bowel resection were excluded. A total of 724 patients were included: 360 in the non-ERAS and 364 in the ERAS cohort. An overall reduction in narcotic usage, measured as oral morphine milliequivalents (MMEs) was observed in the ERAS relative to the non-ERAS group, during the entire hospital stay (MME 34 versus 68, p < 0.001 and within 72 h postoperatively (MME 34 versus 60, p < 0.005). A shorter length of stay and earlier return of bowel function were also observed in the ERAS group. No differences in 30-day readmissions (p = 0.967) or postoperative complications (p = 0.328) were observed. This study demonstrated the benefits of ERAS in Gynecologic Oncology. A significant reduction of postoperative narcotic use, earlier return of bowel function and a shorter postoperative hospital stay was seen in the ERAS compared to traditional perioperative care.